Marketing Strategy Analysis for Small and Medium Enterprises (SMEs) in the Snack Food Industry (Case Study on Lianty Jaya Snack UKM) - Rahmatullah, Arwin yafi; Suwandi, Adam; Selva, Selva; Ningsih, Nurul Hidayati Indra (Review: Journal of Multidisciplinary in Social Sciences, 2024)
Business competition in all sectors is becoming increasingly fierce. Therefore, marketing strategies play an important role in ensuring that products reach their target market and are successful. This study aims to identify the factors that influence and form the basis for the development of marketing strategies at Snack Lianty Jaya. The research method used is descriptive qualitative (exploratory) research. The study was conducted at Lianty Jaya, located in Kekeri Village, Gunungsari Subdistrict, West Lombok Regency. Data collection techniques included interviews, observations, and literature reviews. Data analysis involved the following stages: data reduction, presentation of data after reduction, and drawing conclusions. The results of the study indicate that Lianty Jaya uses a marketing mix strategy and develops its marketing strategy using SWOT analysis.